Towards a Sustainable Future: Examining the Symmetric and Asymmetric Effect of Unstable Macroeconomic Factors on Initial Public Offerings Variability - Mehmood, Waqas; Gharaibeh, Fakir Al; Rizvi, Ifham; Mehmood, Waqar (International Journal of Energy Economics and Policy, 2024)
The research seeks to explore the symmetric and asymmetric effects of renewable energy, technological innovation, and ecological footprint on the variability of initial public offerings in the unique institutional setting of the Pakistani IPO market. The study used yearly data on the Pakistani IPO market and the macroeconomic variables from January 1992 to December 2020. Further, the study employed the linear and Non-Linear ARDL to investigate the symmetric and asymmetric nexus among variables. For that purpose, the stationarity of the variables was predetermined using Augmented Dicker Fuller (ADF) and Phillips Perron (PP) unit root tests. Additionally, the F-bound test verifies that IPO issuance and macroeconomic drivers are co-integrated. The findings show a symmetric and asymmetric relationship between IPO variability and macroeconomic variables under study. Renewable energy and technological innovation have statistically positive effects on IPO variability. On the contrary, the ecological footprint has a significantly negative impact on IPO variability. The weak condition of the Pakistani IPO market could be attributed to the slow adoption of technological innovation, the transition to renewable energy, and a high ecological footprint that attracts stringent regulatory and environmental compliance costs of going public.